Influence of Temperature, Medium, and Storage Duration on Chlamydia trachomatis DNA Detection by PCR - van Dommelen, Laura (American Society for Microbiology, 2013)
We validated the use of stored samples for Chlamydia trachomatis research. C. trachomatis DNA was detected by real-time PCR in clinical (urine and self-taken vaginal swabs) and spiked samples using six different media, five different time points (up to 2 years), and four different temperature conditions. C. trachomatis was detected in all 423 samples, and no clinically relevant degradation impact was detected.